Vulnerability and prison suicide - Liebling, Alison (The British journal of criminology, 1995)
This article summarizes some of the main results from two long-term research projects carried out between 1987 and 1992 on suicide and suicide attempts in prison. Its focus is on those results relating to prisoners. Limitations inherent in the use of statistical data on prison suicide and suicide attempts are demonstrated. The use of long semi-structured interviews, supplemented by observational methods, participation, statistical data, and informal discussions with staff and prisoners is a more appropriate approach to this type of research. The two studies showed that important differences could be found between suicide attempters and other prisoners. Those differences relating to criminal justice histories and background characteristics were differences of degree-suicide attempters had suffered more severe disadvantage, violence, and family problems in their histories and they had had more frequent contact with social services and criminal justice agencies. The more important differences were found in their descriptions of life in prison, which was seen as more difficult for the suicide attempters in almost everyrespect. The article concludes by elaborating on the concept of poor coping in prison and by showing how distinct types of prison suicide can be identified for whom the significance of the immediate environment may differ. Finally, links are drawn between prison suicide and other related literature on prison life